2022
DOI: 10.1071/fp21218
|View full text |Cite
|
Sign up to set email alerts
|

A

Abstract: The crisis of arsenic (As) accumulation in rhizomes threatens the quality and safety of Panax notoginseng (Burk.) F.H. Chen, which is a well-known traditional Chinese herb with a long clinical history. The uptake of arsenate (AsV) could be suppressed by supplying phosphate (Pi), in which Pi transporters play important roles in the uptake of Pi and AsV. Herein, the P. notoginseng Pi transporter-encoding gene PnPht1;3 was identified and characterised under Pi deficiency and AsV exposure. In this study, the open … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 73 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…The mechanism of arsenic uptake by plants varies with the chemical speciation. It has been reported that As(V) uses inorganic Phosphate (Pi) channels for its entry into the plant cell [26]. On the other hand, plants uptake As(III) via various nodulin-26-like intrinsic proteins and silicon transporters due to analogous chemical structures [27].…”
Section: Bioavailability and Mobility Of Arsenic In Soil-plant Systemmentioning
confidence: 99%
“…The mechanism of arsenic uptake by plants varies with the chemical speciation. It has been reported that As(V) uses inorganic Phosphate (Pi) channels for its entry into the plant cell [26]. On the other hand, plants uptake As(III) via various nodulin-26-like intrinsic proteins and silicon transporters due to analogous chemical structures [27].…”
Section: Bioavailability and Mobility Of Arsenic In Soil-plant Systemmentioning
confidence: 99%